El Vers clus de Joan Basset: un poema al·legòric contra el Cisma d’Occident - Romanyà, Alba (Studia Romanica Posnaniensia, 2025)
Joan Basset, a poet active in the early 15th century, wrote his Vers clus around 1415-1416. This enigmatic composition presents an allegorical confrontation between two factions of monstrous figures, led respectively by a dragon and a Turk. Basset’s use of allegory can be explained by the need to disguise a politically charged message in a particularly tense socio-political context at the end of the Western Schism, as well as by an aesthetic tradition that valued poetry of formal and thematic complexity. This article offers a contextualised interpretation of the Vers clus, considering the political events of its time and the literary tradition that frames it. The poem emerges as a work in which political reality is conveyed through symbol.